Economic Learning during The Covid-19 Pandemic in Indonesia: Problems and Solutions - Leny Noviani (Universitas Sebelas Maret, 2021)
The purpose of this study is to provide alternative solutions to problems in implementing economic learning during the Covid-19 pandemic in Indonesia. This research uses a descriptive approach. Data collection was conducted through a survey of 296 economics teachers who teach in senior high school. Data analysis using descriptive analysis. The results showed the main problems faced by economics teachers during the pandemic were: unstable internet network quality, difficulties in preparing media, teaching materials, and developing assessments. Activities undertaken by the teacher to overcome these problems include: using the WhatsApp application for teaching, searching for teaching materials and media from internet sources, using student worksheets in student handbooks. Alternative solutions to overcome the constraints of implementing economic learning during the pandemic are: 1) designing combined online learning using a digital platform that is easily accessible to students, 2) developing media, teaching materials and evaluations that are in accordance with real conditions so that learning remains meaningful for students and can equip students with life skills, 3) optimization of teacher working groups in schools to develop learning strategies, media, teaching materials and evaluation.